(untitled) (Archives of Pediatrics of Uruguay, 2022)
Congenital epulis is a very rare neonatal pathology. It is a benign pedunculated tumor of the jaw mucosa, most frequently located in the upper jaw in a 2-3 / 1 ratio. The case of a newborn, female, term, adequate, vigorous is described. Noting at birth a congenital Epulis that causes suction alterations. Early surgical intervention is perfomed with resolution of the pathology without complications.